Gut dysbiosis as a risk factor of neonatal sepsis among preterm infants - Marsubrin, Putri Maharani Tristanita; Hikmahrachim, Hardya Gustada; Rohsiswatmo, Rinawati; Yulindhini, Maya; Firmansyah, Agus (Indonesian Pediatric Society, 2025)
Background Preterm infants are at high risk of developing sepsis. An imbalance between the normal gut and pathogenic microbiomes, known as dysbiosis, has been proposed as a condition that leads to neonatal sepsis. Objective To assess for an association between gut dysbiosis and neonatal sepsis. Methods A prospective cohort study was conducted involving very preterm or very low birth weight infants admitted to the Neonatal Unit, Cipto Mangunkusumo Hospital, Jakarta, from November 2019 to January 2021. The primary outcome was proven and/or clinical neonatal sepsis. The independent variable was gut dysbiosis, defined as a ratio of normal-to-pathogenic gut microbiome <1.0. Gut microbiome analysis was performed using a polymerase chain reaction test from a fecal specimen. Multivariate analysis using multiple logistic regression was conducted with adjustments for potential confounders. Results Forty-three infants were recruited during the study period, with a median gestational age of 30 (range 25-36) weeks and birth weight of 1,170 (range 630-1855) grams. Among them, 28 (65.1%) infants had dysbiosis and 25 (58.2%) developed sepsis. The incidence of sepsis was higher among infants with dysbiosis (20 infants; 71.4%) than those without dysbiosis (5 infants; 33.3%). Dysbiosis and hemodynamically significant patent ductus arteriosus increased the risk of sepsis, with aOR 6.93 (95%CI 1.04 to 46.14; P=0.045) and aOR 22.7 (95%CI 1.45 to 355.29; P=0.026), respectively, after adjusting for sex, birthweight, maternal and infant morbidities, as well as maternal and infant vitamin D status. Conclusion Gut dysbiosis is a risk factor for neonatal sepsis. Maintaining the balance of the gut microbiome is essential from the first day of life.